Hollow electron lenses for beam collimation at the High-Luminosity Large Hadron Collider (HL-LHC). (31st March 2021) - Redaelli, S.; Appleby, R.B.; Bruce, R.; Brüning, O.; Kolehmainen, A.; Ferlin, G.; Foussat, A.; Giovannozzi, M.; Hermes, P.; Mirarchi, D.; Perini, D.; Rossi, A.; et al.
Abstract: Electrons lenses produce a high-intensity electron beam and have a variety of applications to circular hadron accelerators. Electron beams of different transverse cross sections and distributions may be designed, depending on the desired application, and they are produced and steered along the orbit of the hadron beam, overlapping with it for typical distances of a few meters before being deflected away and disposed of. Hollow electron beams find applications to high-intensity beam collimation for machines like the CERN Large Hadron Collider (LHC). Such devices can be integrated in a collimation system to improve the halo-cleaning performance through an active control of the halo dynamics: the annular distribution of the electrons excites resonantly the beam tails surrounding the beam core, while the core itself remains unperturbed, as ideally it only "sees" the field-free "hole" in the electron distribution. Hollow electron lenses are part of the upgrade baseline of the High-Luminosity project of the LHC (HL-LHC) and will be installed in the machine during a long shutdown in 2025–2027 to mitigate effects from beam losses so to improve the collimation system performance. This paper describes the hollow electron lens project within the HL-LHC collimation upgrade.